2019
DOI: 10.1007/s00262-018-02294-5
|View full text |Cite
|
Sign up to set email alerts
|

The route of administration dictates the immunogenicity of peptide-based cancer vaccines in mice

Abstract: Vaccines consisting of synthetic peptides representing cytotoxic T lymphocyte (CTL) epitopes have long been considered as a simple and cost-effective approach to treat cancer. However, the efficacy of these vaccines in the clinic in patients with measurable disease remains questionable. We believe that the poor performance of peptide vaccines is due to their inability to generate sufficiently large CTL responses that are required to have a positive impact against established tumors. Peptide vaccines to elicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…5,6 We have developed two vaccine strategies consisting of synthetic epitope peptides mixed with Toll-like receptor 3 (TLR3) agonist, polyinosinic-polycytidylic acid (poly-IC), and anti-CD40 Ab (called TriVax) or with poly-IC alone (called BiVax) capable of eliciting vast CTL responses in mouse cancer models. [5][6][7][8][9] Furthermore, TriVax with the TLR7 agonist gardiquimod, instead of poly-IC, generated vast anti-tumor HTL responses by adding an anti-OX40 agonist Ab. 55 Importantly, effective T-cell responses could be induced by injecting these vaccines systemically (intravenously or intramuscularly) with two sequential immunizations (prime and boost protocol), [5][6][7]9 indicating that for practical use of peptide vaccines, systemic immunizations may be more effective than subcutaneous local administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 We have developed two vaccine strategies consisting of synthetic epitope peptides mixed with Toll-like receptor 3 (TLR3) agonist, polyinosinic-polycytidylic acid (poly-IC), and anti-CD40 Ab (called TriVax) or with poly-IC alone (called BiVax) capable of eliciting vast CTL responses in mouse cancer models. [5][6][7][8][9] Furthermore, TriVax with the TLR7 agonist gardiquimod, instead of poly-IC, generated vast anti-tumor HTL responses by adding an anti-OX40 agonist Ab. 55 Importantly, effective T-cell responses could be induced by injecting these vaccines systemically (intravenously or intramuscularly) with two sequential immunizations (prime and boost protocol), [5][6][7]9 indicating that for practical use of peptide vaccines, systemic immunizations may be more effective than subcutaneous local administration.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] While peptide vaccines might be regarded as insufficient to elicit robust anti-tumor responses because of disappointing results in past clinical trials, recent research progress has shown that the weak efficacy of peptide vaccines might be overcome by optimization of peptide conformation, routes of administration and the use of effective immune adjuvants. [5][6][7] Moreover, combination of peptide vaccines with immune-checkpoint inhibitors has demonstrated significant anti-tumor effects in preclinical studies. 8,9 Thus, the time has arrived to reconsider the clinical effects of peptide vaccines as well as their advantages, such as ease of synthesis and costeffectiveness compared to other immunotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, intravenous immunization of a peptide vaccine with poly-ICLC as an adjuvant generated significantly higher cytotoxic T lymphocyte (CTL) responses compared to subcutaneous delivery and resulted in more robust anti-tumor effects [ 187 ]. In addition, this study found that the use of amphiphilic antigen constructs such as palmitoylated peptides are more immunogenic that SLPs, which are routinely used in the clinic [ 187 ]. This is likely due to their ability to self-assemble into nanoparticles [ 188 ].…”
Section: Route Of Administrationmentioning
confidence: 99%
“…can induce stronger CTL responses compared to responses caused by subcutaneous (s.c.) or intramuscular (i.m.) injections 109.…”
Section: Peptide-based Cancer Vaccinementioning
confidence: 99%